Valuable agronomic traits of chufa (Cyperus esculentus L.) accessions from the VIR collection: methods of preparing nodules for long-term storage - N. G. Kon’kova; G. F. Safina (Труды по прикладной ботанике, генетике и селекции)
Background. Chufa is one of the most promising rare oilseed crops. The issues of preserving and obtaining highquality seed material are very important. The development of long-term genebank storage techniques for chufa nodules is a pressing task.Materials and methods. We studied 18 chufa germplasm accessions of various origin. The field study was conducted in 2010–2012 under the environmental conditions of Krasnodar Territory, Russia. Protein and oil content was analyzed according to the guidelines on the methods of quality control and safety of bioactive food additives (R 4.1.1672-03…, 2004); vitamin E according to the guidelines on the methods of analyzing the quality and safety of food products (Skurikhin, Tutelyan, 1987); fatty acid composition in line with IUPAC (1979) and GOST R 512677-2006, using an IIRGCS chromatograph.Results and conclusions. The study of valuable agronomic characters in chufa accessions showed that the height of plants varied from 49 to 69 cm; the number of nodules per plant from 80 to 110 pcs; the weight of nodules per plant from 18 to 49 g; the weight of nodules per plot (1 m2 ) from 101 to 393 g. Their oil content varied from 13.1 to 21.06 g/100 g, and protein content from 6 to 10%. Chufa accessions contained large amount of vitamin E: 19.23 to 35.23 mg/100 g. The content of saturated fatty acids in chufa oil was 17.75 to 20.99%, monounsaturated fatty acids from 68.21 to 71.55%, and polyunsaturated fatty acids from 9.94 to 12.17%. A technique of preparing chufa nodules for long-term storage was developed. The optimal time to assess germination energy is four days, with 11 days for germination percentage. Storage of chufa nodules for three years at a temperature of +20°C causes a decrease in their germination by 15–16%. When stored under low positive (+4°C) or negative temperatures (–18°C and –196°C), their germination percentage remained unchanged.